1999
DOI: 10.1074/jbc.274.7.3994
|View full text |Cite
|
Sign up to set email alerts
|

Formyl Peptide Receptor Signaling in HL-60 Cells through Sphingosine Kinase

Abstract: Sphingosine-1-phosphate (SPP) produced from sphingosine by sphingosine kinase has recently been reported to act as intracellular second messenger for a number of plasma membrane receptors. In the present study, we investigated whether the sphingosine kinase/SPP pathway is involved in cellular signaling of the G i proteincoupled formyl peptide receptor in myeloid differentiated human leukemia (HL-60) cells. Receptor activation resulted in rapid and transient production of SPP by sphingosine kinase, which was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 33 publications
4
93
1
Order By: Relevance
“…It therefore appears that the activation of GTP-binding proteins is required in the toxin-activated SM metabolic system. Alemany et al (57) reported that the direct activation of heterotrimeric GTP-binding protein increased production of S1P in HL-60 cells, and sphingosine kinase was activated by GTP␥S. Pertussis toxin inhibited the ␣-toxin-induced hydrolysis of SM in the cell lysates but had no effect on the SMase activity of ␣-toxin, suggesting that ␣-toxin activates endogenous SMase through pertussis toxin-sensitive G i type GTP-binding protein.…”
Section: ␣-Toxin-induced Hemolysis and Sphingomyelin Metabolismmentioning
confidence: 99%
“…It therefore appears that the activation of GTP-binding proteins is required in the toxin-activated SM metabolic system. Alemany et al (57) reported that the direct activation of heterotrimeric GTP-binding protein increased production of S1P in HL-60 cells, and sphingosine kinase was activated by GTP␥S. Pertussis toxin inhibited the ␣-toxin-induced hydrolysis of SM in the cell lysates but had no effect on the SMase activity of ␣-toxin, suggesting that ␣-toxin activates endogenous SMase through pertussis toxin-sensitive G i type GTP-binding protein.…”
Section: ␣-Toxin-induced Hemolysis and Sphingomyelin Metabolismmentioning
confidence: 99%
“…Direct Depletion of ER Calcium Stores Activates S1P Synthesis-The stimulation of S1P production from sphingosine by GPC agonists is well known (39,40), but if S1P links store depletion to SOCE, then direct store depletion should elicit S1P synthesis. This has not been examined.…”
Section: Fig 2 S1p Does Not Induce Emptying Of Pmn Calcium Storesmentioning
confidence: 99%
“…In addition to its extracellular actions, S1P functions as a second messenger in the regulation of Ca 2+ homeostasis, 24,28,50,51 and suppression of apoptosis. 11,12,14,23,31,52 Although the intracellular targets of S1P remain to be identified, several lines of evidence support the second messenger role of S1P: (1) dihydro-S1P binds to and activates all of the identified S1PRs, but it does not mimic all of the effects of S1P, especially those related to cell survival; 30 (2) yeast cells do not possess GPCRs, yet the abundance of phosphorylated long-chain sphingoid bases regulates environmental stress responses, cell proliferation, and cell survival in a manner reminiscent of the function of S1P in mammalian cells; (3) in plants, which do not express S1PRs, S1P regulates Ca 2+ homeostasis and ion channels; 53 and (4) microinjection of S1P into, or photolysis of caged S1P within, mammalian cells induces both Ca 2+ mobilization 54 and cell proliferation.…”
Section: S1p As An Intracellular Second Messengermentioning
confidence: 99%